Dreams, the Female Gaze, and the City of Paris: Urban Landscapes through the Writings of the Surrealist Movement - Barreiro León, Bárbara (Escritura e Imagen, 2021)
From the time of the Renaissance, treaties on architecture, odes to the arts, and the study of their canons through written sources, have served to defend, emphasise, or proclaim the validity of different artistic forms and styles. In this way, programmes and manifestos have reinforced the character of organisations and movements through their fundamental ideas. The artistic Avantgardes have thus used this literary resource to lay the theoretical foundations for their future artistic contributions, being able to justify without any qualifications their most extravagant occurrences. The Avant-garde manifesto shall therefore be considered a literary contribution written in the first place for the subsequent development of the artistic and creative activity of the group or school. The Surrealist Movement generated a lot of written work because the founders, André Breton, Louis Aragon, and Philippe Soupault, were writers. Some of these texts included the Movement’s two manifestos, periodicals such as Le Surréalisme au service de la révolution, Littérature, or Minotaure, and individual writings that were penned by Breton and Aragon. This study will relate the Surrealist written work with the Movement’s idea of the city and its urban imaginary.
Keywords: Surrealism; Literature; Photography; City; Urbanism